Rubber composition for side tread
A rubber composition with specific isoprene and butadiene content, large particle size silica, and guanidine-based vulcanization accelerator addresses the balance of hardness, tensile strength, and heat generation in side tread tires, enhancing tire performance.
Patent Information
- Application Number
- JP2023011188
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-01-27
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2043-01-27
AI Technical Summary
Existing rubber compositions for side treads in tires face challenges in maintaining good hardness and tensile strength while suppressing heat generation and elongation loss over time, with methods like reducing carbon black or incorporating silica not providing sufficient balance.
A rubber composition comprising 35-55% isoprene rubber, 45-65% butadiene rubber, large particle size silica and carbon black, sulfur-containing silane coupling agent, and a guanidine-based vulcanization accelerator, with specific ratios and amounts to balance hardness, tensile strength, and low heat build-up.
The composition maintains good hardness and tensile strength, suppresses elongation loss over time, and reduces heat build-up effectively, achieving well-balanced performance for side tread applications.
Smart Images

Figure 0007602152000002 
Figure 0007602152000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition for a side tread intended primarily for use in a side tread layer of a tire. [Background technology]
[0002] In pneumatic tires, there is a demand for improving fuel efficiency during driving in order to reduce the environmental load. For this reason, efforts have been made to suppress heat generation in rubber compositions constituting various parts of pneumatic tires. In recent years, in order to further improve fuel efficiency, for example, studies have been made on suppressing heat generation in rubber compositions constituting the side tread rubber layer of pneumatic tires (rubber compositions for side treads).
[0003] As an index of heat generation of a rubber composition, tan δ at 60°C (hereinafter referred to as "tan δ(60°C)") by dynamic viscoelasticity measurement is generally used, and the smaller the tan δ(60°C) of the rubber composition, the smaller the heat generation. As a method for decreasing the tan δ(60°C) of the rubber composition, for example, the amount of filler such as carbon black or the like is decreased, or the particle size of the carbon black is increased. Alternatively, it has been proposed to compound silica having a large particle size (see, for example, Patent Document 1). However, these methods do not necessarily provide sufficient rubber hardness, and there is concern about the effect on the tensile strength required for a rubber composition for side treads. Furthermore, there is concern about the deterioration over time (particularly the decrease in elongation at break) of the rubber composition stored in an unvulcanized state. Therefore, in the rubber composition for side treads, further measures are required to improve low heat generation (tan δ(60°C)) while maintaining good hardness and tensile strength and suppressing the decrease in elongation at break over time. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-001889 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a rubber composition for side treads which maintains good hardness and tensile strength while suppressing the decrease in breaking elongation over time of a rubber composition stored in an unvulcanized state, and which has improved low heat build-up properties (tan δ(60°C)), thereby achieving a good balance between these performance properties to a high degree. [Means for solving the problem]
[0006] The rubber composition for side treads of the present invention, which achieves the above object, has a CTAB adsorption specific surface area of 60 m for a diene rubber containing 35% by mass to 55% by mass of isoprene rubber and 45% by mass to 65% by mass of butadiene rubber. 2 / g~100m 2 / g silica, CTAB adsorption specific surface area is 30m 2 / g~100m 2 A rubber composition for a side tread, which is compounded with carbon black having a silica content of 0.1 to 0.5 parts by mass, a sulfur-containing silane coupling agent, and a guanidine-based vulcanization accelerator, wherein the amount of the silica compounded with respect to 100 parts by mass of the diene rubber is 5 parts by mass or more and 50 parts by mass or less, the total amount of the silica and the carbon black compounded is less than 55 parts by mass, and a ratio Ma / Ms of the amount of the guanidine-based vulcanization accelerator Ma to the amount Ms of the silica compounded is 0.02 to 0.08. The proportion of the butadiene rubber synthesized using a neodymium-based catalyst contained in the butadiene rubber is 100 mass %. It is characterized by: Effect of the Invention
[0007] The rubber composition for side tread of the present invention, which is made of the above-mentioned blend, maintains good hardness and tensile strength, and improves low heat build-up while suppressing the decrease in breaking elongation over time, thereby achieving a good balance between these performances. 2 / g~100m 2By using large particle size silica with a particle size of 0.1 to 1.0 μm / g, tan δ(60°C) can be reduced and low heat buildup can be improved. In addition, the above-mentioned setting of the compounding ratio of large particle size silica and carbon black is also expected to reduce tan δ(60°C) (improvement of low heat buildup). On the other hand, by compounding an appropriate amount of a guanidine vulcanization accelerator with respect to silica as a vulcanization accelerator, hardness and tensile strength can be maintained well and a decrease in breaking elongation over time can be suppressed. Through these cooperation, low heat buildup can be improved while maintaining good hardness and tensile strength and suppressing a decrease in breaking elongation over time, and the physical properties required for the side tread rubber layer can be exhibited well.
[0008] In the present invention, it is preferable that the butadiene rubber contains a butadiene rubber synthesized by a neodymium-based catalyst, and optionally contains a terminal-modified butadiene rubber for silica. At this time, it is preferable that the ratio of the butadiene rubber synthesized by a neodymium-based catalyst contained in the butadiene rubber is 69% by mass to 100% by mass, the ratio of the terminal-modified butadiene rubber for silica is 0% by mass to 31% by mass, and the mixing ratio of the terminal-modified butadiene rubber for silica to 100% by mass of the diene rubber is less than 20% by mass. By containing the butadiene rubber synthesized by a neodymium-based catalyst and the terminal-modified butadiene rubber for silica in this way, it is advantageous to maintain the hardness and tensile strength well, and improve the low heat generation while suppressing the decrease in the breaking elongation over time.
[0009] In the present invention, other vulcanization accelerators than the guanidine-based vulcanization accelerator are blended, and the ratio Ma / Mt of the blending amount Ma of the guanidine-based vulcanization accelerator to the total amount Mt of the vulcanization accelerator consisting of the guanidine-based vulcanization accelerator and the other vulcanization accelerator is preferably 0.2 to 0.5. Also, the blending amount Ma of the guanidine-based vulcanization accelerator is preferably 0.5 parts by mass or more per 100 parts by mass of the diene rubber. By blending an appropriate amount of the guanidine-based vulcanization accelerator in this way, the rubber composition stored in an unvulcanized state can be improved in low heat build-up while suppressing the decrease in elongation at break over time, and these performances can be achieved in a well-balanced manner.
[0010] The rubber composition for side treads of the present invention can be suitably used for the side tread rubber layer of a tire. A tire having a side tread rubber layer made of the rubber composition for side treads of the present invention can reduce rolling resistance and improve fuel economy performance while maintaining the hardness and tensile strength required for the side tread rubber layer and suppressing the decrease in breaking elongation over time due to the excellent physical properties of the rubber composition for side treads of the present invention. [Brief description of the drawings]
[0011] [Figure 1] 1 is a meridian cross-sectional view showing an example of a pneumatic tire using the rubber composition for a side tread of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The configuration of the present invention will be described in detail below with reference to the accompanying drawings.
[0013] As shown in FIG. 1, a pneumatic tire using the rubber composition for a side tread of the present invention includes a tread portion 1, a pair of sidewall portions 2 arranged on both sides of the tread portion 1, and a pair of bead portions 3 arranged on the tire radially inner side of the sidewall portions 2. In FIG. 1, the symbol CL indicates the tire equator. Although not depicted because FIG. 1 is a meridian cross section, the tread portion 1, the sidewall portions 2, and the bead portions 3 each extend in the tire circumferential direction to form an annular shape, thereby forming a basic toroidal structure of a pneumatic tire. The following description using FIG. 1 is basically based on the meridian cross section shown in the figure, but each tire component extends in the tire circumferential direction to form an annular shape.
[0014] A carcass layer 4 is installed between a pair of left and right bead portions 3. This carcass layer 4 includes a plurality of reinforcing cords extending in the tire radial direction, and is folded back from the inner side to the outer side in the tire width direction around a bead core 5 arranged in each bead portion 3. A bead filler 6 is arranged on the outer periphery of the bead core 5, and this bead filler 6 is wrapped by the main body and the folded back portion of the carcass layer 4. Meanwhile, a plurality of belt layers 7 (two layers in FIG. 1) are embedded on the outer periphery side of the carcass layer 4 in the tread portion 1. Each belt layer 7 includes a plurality of reinforcing cords inclined with respect to the tire circumferential direction, and the reinforcing cords are arranged so as to cross each other between the layers. In these belt layers 7, the inclination angle of the reinforcing cords with respect to the tire circumferential direction is set to, for example, a range of 10° to 40°. Furthermore, a belt reinforcing layer 8 (two layers, a full cover 8a covering the entire width of the belt layer 7 and an edge cover 8b locally covering the end portion of the belt layer 7) is provided on the outer periphery side of the belt layer 7. The belt reinforcing layer 8 includes organic fiber cords oriented in the tire circumferential direction. In the belt reinforcing layer 8, the organic fiber cords are set at an angle of, for example, 0° to 5° with respect to the tire circumferential direction.
[0015] A tread rubber layer 10 is disposed on the outer peripheral side of the carcass layer 4 in the tread portion 1, a side tread rubber layer 20 is disposed on the outer peripheral side (outside in the tire width direction) of the carcass layer 4 in the sidewall portion 2, and a rim cushion rubber layer 30 is disposed on the outer peripheral side (outside in the tire width direction) of the carcass layer 4 in the bead portion 3. The rubber composition for side tread of the present invention is used for the side tread rubber layer 20 of such a tire. Therefore, the basic structure of other parts is not limited to the above-mentioned structure. The side tread rubber layer 20 is a layer that is required to have excellent breaking elongation (flex fatigue resistance) because it is the part of the tire that is most bent during driving, unlike the tread rubber layer 10 that contacts the road surface and the rim cushion rubber layer 30 that contacts the rim (not shown). In addition, it is a layer that is required to have excellent cut resistance because it tends to be frequently damaged by external damage.
[0016] The tire in which the rubber composition for side tread of the present invention is used is preferably a pneumatic tire (a tire filled with air, an inert gas such as nitrogen, or other gas) as described above, but may be a non-pneumatic tire. In the case of a non-pneumatic tire, the rubber composition for side tread of the present invention can be used in the portion located between the portion that contacts the road surface (a portion corresponding to the tread rubber layer 10 in a pneumatic tire) and the portion that contacts the rim when mounted on the rim (a portion corresponding to the rim cushion rubber layer 30 in a pneumatic tire).
[0017] In the rubber composition for side treads of the present invention, the rubber component is a diene rubber, which necessarily includes an isoprene rubber and a butadiene rubber. As the butadiene rubber, a butadiene rubber polymerized using a neodymium catalyst (hereinafter, sometimes referred to as Nd-BR) is preferably used. Alternatively, it is preferable to use Nd-BR in combination with a terminal-modified butadiene rubber for silica described below. In this way, by using an isoprene rubber and a butadiene rubber (particularly Nd-BR or a terminal-modified butadiene rubber for silica), it is possible to improve tensile strength, low heat build-up, and fatigue resistance.
[0018] Examples of isoprene-based rubber include various natural rubbers, epoxidized natural rubbers, and various synthetic polyisoprene rubbers. Among these isoprene-based rubbers, natural rubbers are particularly suitable. The amount of isoprene-based rubber is 35% by mass to 55% by mass, preferably 37.5% by mass to 52.5% by mass, and more preferably 40% by mass to 50% by mass, based on 100% by mass of diene-based rubber. By blending such an amount of isoprene-based rubber, it is possible to improve the tensile strength and fatigue resistance in a well-balanced manner. If the amount of isoprene-based rubber is less than 35% by mass, the tensile strength decreases. If the amount of isoprene-based rubber is more than 55% by mass, the fatigue resistance deteriorates.
[0019] As the butadiene rubber, those generally used in rubber compositions for tires, such as unmodified butadiene rubber and modified butadiene rubber, can be used. However, from the viewpoint of improving low heat generation, butadiene rubber polymerized using a neodymium-based catalyst (Nd-BR) is preferably used as described above. The compounding amount of butadiene rubber is 45% by mass to 65% by mass, preferably 47.5% by mass to 62.5% by mass, and more preferably 50% by mass to 60% by mass, based on 100% by mass of diene rubber. By compounding such an amount of butadiene rubber, tensile strength and fatigue resistance can be improved in a well-balanced manner. If the compounding amount of butadiene rubber is less than 45% by mass, fatigue resistance decreases. If the compounding amount of butadiene rubber is more than 65% by mass, tensile strength deteriorates.
[0020] The Nd-BR preferably used in the present invention is a known material, and is a butadiene rubber polymerized using a neodymium-based catalyst such as neodymium alone, a compound of neodymium with other metals, or an organic neodymium compound. Butadiene rubber synthesized using these neodymium-based catalysts has the characteristics of a high molecular weight and a sharp molecular weight distribution. As the Nd-BR, commercially available products can be used, such as Buna CB22 and Buna CB24 manufactured by Arlanxeo. Since the butadiene rubber is polymerized using a neodymium-based catalyst in this way, it is possible to improve the low heat generation property more effectively than butadiene rubber polymerized using other catalysts (e.g., nickel or cobalt).
[0021] When using Nd-BR as the butadiene rubber, the specific type of Nd-BR is not particularly limited, but the vinyl content is preferably 0% by mass to 1% by mass, more preferably 0% by mass to 0.8% by mass, and even more preferably 0% by mass to 0.5% by mass. Such a low vinyl content is advantageous for improving low heat generation. If the vinyl content in the Nd-BR exceeds 1% by mass, the effect of improving low heat generation cannot be expected sufficiently. The vinyl content of the butadiene rubber (Nd-BR) is measured by infrared spectroscopy (Hampton method). The increase or decrease in the vinyl content in the butadiene rubber can be appropriately adjusted by a normal method, such as by changing the type of catalyst (the specific type of the neodymium-based catalyst described above).
[0022] When Nd-BR is used as the butadiene rubber, the compounding amount is 69% by mass to 100% by mass, preferably 73% by mass to 100% by mass, more preferably 77% by mass to 100% by mass, based on 100% by mass of the butadiene rubber. For example, when the compounding amount of the butadiene rubber is 65% by mass in 100% by mass of the diene rubber, the compounding amount of the Nd-BR is 45% by mass to 65% by mass, preferably 47.5% by mass to 65% by mass, more preferably 50% by mass to 65% by mass, based on 100% by mass of the diene rubber. By compounding such an amount of Nd-BR, it is possible to effectively improve the low heat build-up property. If the compounding amount of the Nd-BR is less than 69% by mass based on 100% by mass of the butadiene rubber, the fatigue resistance decreases.
[0023] In the present invention, the butadiene rubber may be a terminal-modified butadiene rubber for silica, in combination with the above-mentioned Nd-BR. The terminal-modified butadiene rubber for silica is a butadiene rubber in which both or one of the molecular ends are modified with a functional group reactive with the silanol group on the silica surface. Examples of the functional group reactive with the silanol group include at least one selected from a polyorganosiloxane group, a hydroxyl group-containing polyorganosiloxane structure, an alkoxysilyl group, a hydroxyl group, an aldehyde group, a carboxyl group, an amino group, an imino group, an epoxy group, an amide group, a thiol group, and an ether group. Among these, a polyorganosiloxane group, a hydroxyl group-containing polyorganosiloxane structure, an alkoxysilyl group, a hydroxyl group, and an amino group are preferred. In addition, a combination of a plurality of these functional groups (for example, two types of amino groups and alkoxysilyl groups) may be used. By including at least one type of terminal-modified butadiene rubber for silica as the butadiene rubber, the affinity with the large particle size silica described below is improved, and this is advantageous in improving low heat build-up while maintaining good hardness and tensile strength and suppressing a decrease in elongation at break over time.
[0024] When the butadiene rubber is a terminal-modified butadiene rubber for silica, its compounding amount is 0% by mass to 31% by mass, preferably 0% by mass to 27% by mass, more preferably 0% by mass to 23% by mass, based on 100% by mass of the butadiene rubber. However, the compounding amount of the terminal-modified butadiene rubber for silica is less than 20% by mass based on 100% by mass of the diene rubber. For example, when the compounding amount of the butadiene rubber is 65% by mass in 100% by mass of the diene rubber, the compounding amount of the terminal-modified butadiene rubber for silica is 0% by mass or more and less than 20% by mass, preferably 0% by mass to 17.5% by mass, more preferably 0% by mass to 15% by mass, based on 100% by mass of the diene rubber. By compounding such an amount of the terminal-modified butadiene rubber for silica, the effect of increasing the affinity with the large particle size silica described later can be sufficiently ensured, and it is advantageous for improving the low heat generation while maintaining good hardness and tensile strength and suppressing the decrease in the breaking elongation over time. If the compounding amount of the terminal-modified butadiene rubber for silica exceeds 31% by mass relative to 100% by mass of the butadiene rubber, the elongation at break deteriorates.
[0025] The rubber composition for side tread of the present invention may contain other diene rubbers in addition to the above-mentioned isoprene rubber and butadiene rubber (Nd-BR, silica-terminal modified butadiene rubber). As the other diene rubber, rubbers that can be generally used in rubber compositions for tires can be used. For example, styrene butadiene rubber can be exemplified. These other diene rubbers can be used alone or as any blend.
[0026] In the present invention, silica and carbon black are always blended as fillers into the diene rubber. As the silica used in the present invention, for example, silica usually used in rubber compositions for tires, such as wet process silica, dry process silica, or surface-treated silica, can be used. However, silica having a CTAB adsorption specific surface area of 60 m 2 / g~100m 2 / g, preferably 65m 2 / g~95m 2 / g, more preferably 70m 2 / g~90m2 / g. By using silica with a large particle size, tan δ(60°C) can be reduced and low heat generation can be improved. The CTAB adsorption specific surface area of silica is 60m 2 If the CTAB adsorption specific surface area of silica is less than 100m 2 If the silica satisfies the above-mentioned conditions, it may be appropriately selected from commercially available silicas and used, and silica obtained by a conventional manufacturing method may also be used.
[0027] The compounding amount Ms of silica is 5 parts by mass or more and 50 parts by mass or less, preferably 10 parts by mass to 45 parts by mass, and more preferably 15 parts by mass to 40 parts by mass, per 100 parts by mass of the diene rubber. By compounding an appropriate amount of silica in this way, low heat buildup can be effectively achieved. If the compounding amount Ms of silica is less than 5 parts by mass, the tensile strength decreases. If the compounding amount Ms of silica is more than 50 parts by mass, the low heat buildup deteriorates.
[0028] The carbon black used in the present invention is a carbon black having a CTAB adsorption specific surface area of 30 m among the carbon blacks usually used in rubber compositions for tires. 2 / g~100m 2 / g, preferably 30m 2 / g~85m 2 / g, more preferably 30m 2 / g~70m 2 The use of such carbon black is advantageous in improving low heat build-up while maintaining good hardness and tensile strength and suppressing the decrease in breaking elongation over time. 2 If the CTAB adsorption specific surface area of carbon black is less than 100 m 2 If it exceeds 1 / g, the low heat build-up property decreases.
[0029] In the present invention, silica and carbon black are always used in combination as described above. At this time, the total amount (Ms+Mc) of silica blended amount Ms and carbon black blended amount Mc is less than 55 parts by mass, preferably 20 parts by mass to 55 parts by mass, more preferably 25 parts by mass to 50 parts by mass, relative to 100 parts by mass of the diene rubber. By blending silica and carbon black in an appropriate amount in this way, it is possible to maintain good hardness and tensile strength, and improve low heat buildup while suppressing the decrease in elongation at break over time. If the total amount of silica and carbon black blended is 55 parts by mass or more, low heat buildup is reduced. The amount of carbon black blended alone is not particularly limited, but is preferably 5 parts by mass to 30 parts by mass, more preferably 5 parts by mass to 25 parts by mass.
[0030] The rubber composition of the present invention may contain fillers other than silica and carbon black, such as clay, talc, calcium carbonate, mica, aluminum hydroxide, and other materials that are generally used in rubber compositions for tires.
[0031] In the rubber composition for side tread of the present invention, a sulfur-containing silane coupling agent is necessarily blended when the silica is blended. By blending the sulfur-containing silane coupling agent, the dispersibility of the silica in the diene rubber can be improved. Examples of the sulfur-containing silane coupling agent include bis-(3-triethoxysilylpropyl) tetrasulfide, bis(3-triethoxysilylpropyl) disulfide, 3-trimethoxysilylpropyl benzothiazole tetrasulfide, γ-mercaptopropyl triethoxysilane, and 3-octanoylthiopropyl triethoxysilane. Among these, those having a tetrasulfide bond in the molecule can be preferably used. The blending amount of the silane coupling agent is preferably less than 10% by mass, more preferably 3% to 9% by mass, based on the blending amount of the silica. If the blending amount of the silane coupling agent is 10% by mass or more of the silica blending amount, the silane coupling agents condense with each other, and the desired hardness and strength of the rubber composition cannot be obtained.
[0032] The rubber composition for side tread of the present invention necessarily contains a vulcanization accelerator. As the vulcanization accelerator, those generally used in rubber compositions for tires can be used, and examples thereof include guanidine-based vulcanization accelerators, sulfenamide-based vulcanization accelerators, and thiuram-based vulcanization accelerators. However, in the present invention, in consideration of the blending of large particle size silica as described above, among these, a guanidine-based vulcanization accelerator is necessarily blended. That is, while the blending of large particle size silica tends to decrease the vulcanization rate, blending a guanidine-based vulcanization accelerator can accelerate vulcanization, which is advantageous for obtaining desired rubber properties. Furthermore, in the present invention, blending a guanidine-based vulcanization accelerator can suppress deterioration of the unvulcanized rubber composition over time during storage (decrease in elongation at break over time). Note that vulcanization accelerators other than the guanidine-based vulcanization accelerator can be used in combination as desired. When two types of vulcanization accelerators are used, examples of the vulcanization accelerator to be combined with the guanidine-based vulcanization accelerator include a sulfenamide-based vulcanization accelerator and a thiuram-based vulcanization accelerator, and among these, the sulfenamide-based vulcanization accelerator can be preferably used.
[0033] Examples of the guanidine vulcanization accelerator include diphenyl guanidine and di-orthotolyl guanidine. Examples of the sulfenamide vulcanization accelerator include N,N-dicyclohexyl-1,3-benzothiazole-2-sulfenamide (DZ), N-cyclohexyl-2-benzothiazole sulfenamide (CZ), N-oxydiethylene-2-benzothiazole sulfenamide (OBS), and N-(tert-butyl)benzothiazole-2-sulfenamide (NS). Examples of the thiuram vulcanization accelerator include tetramethylthiuram monosulfide and tetramethylthiuram disulfide.
[0034] When compounding the guanidine vulcanization accelerator, the ratio Ma / Ms of the compounding amount Ma of the guanidine vulcanization accelerator to the compounding amount Ms of the silica described above is set to 0.02 to 0.08, preferably 0.02 to 0.07, and more preferably 0.03 to 0.06. In this way, compounding an appropriate amount of the guanidine vulcanization accelerator with respect to the large particle size silica described above is advantageous in suppressing the decrease in the breaking elongation of the rubber composition in an unvulcanized state over time. If the ratio Ma / Ms of the compounding amount Ma of the guanidine vulcanization accelerator to the compounding amount Ms of the silica is less than 0.02, there is a risk that the breaking elongation will occur over time when the rubber composition is stored in an unvulcanized state. If the ratio Ma / Ms of the compounding amount Ma of the guanidine vulcanization accelerator to the compounding amount Ms of the silica exceeds 0.08, the hardness cannot be maintained well and the low heat generation property is also deteriorated.
[0035] In the case where the vulcanization accelerator contains a guanidine-based vulcanization accelerator and a vulcanization accelerator other than a guanidine-based vulcanization accelerator (other vulcanization accelerator), the ratio Ma / Mt of the amount of the guanidine-based vulcanization accelerator to the total amount Mt of the vulcanization accelerator (the sum of the amount of the guanidine-based vulcanization accelerator Ma and the amount of the other vulcanization accelerators to 100 parts by mass of the diene rubber) is preferably 0.2 to 0.5, more preferably 0.25 to 0.5, and even more preferably 0.3 to 0.5. In this way, it is advantageous to improve low heat buildup by blending an appropriate amount of the guanidine-based vulcanization accelerator to the total amount of the vulcanization accelerator. If the ratio Ma / Mt is less than 0.2, there is a risk that the breaking elongation will decrease when the rubber composition is stored in an unvulcanized state. If the ratio Ma / Mt exceeds 0.5, tan δ (60°C) will deteriorate, and the effect of improving low heat buildup will be limited.
[0036] Furthermore, when compounding the guanidine vulcanization accelerator, the compounding amount Ma is preferably 0.5 parts by mass or more, more preferably 0.5 to 2 parts by mass, and even more preferably 0.5 to 1.5 parts by mass, per 100 parts by mass of the rubber component. By compounding an appropriate amount of the guanidine vulcanization accelerator in this way, it is advantageous to suppress the decrease in the breaking elongation of the unvulcanized rubber composition over time. If the compounding amount Ma of the guanidine vulcanization accelerator is less than 0.5 parts by mass, there is a risk that the breaking elongation will decrease when the rubber composition is stored in an unvulcanized state.
[0037] Other compounding agents than those mentioned above can be added to the rubber composition for side tread of the present invention. Examples of other compounding agents include various compounding agents generally used in rubber compositions for tires, such as vulcanizing or crosslinking agents, antiaging agents, and liquid polymers. The compounding amounts of these compounding agents can be conventionally used amounts as long as they do not go against the object of the present invention. In addition, as the kneading machine, a normal rubber kneading machine, such as a Banbury mixer, a kneader, or a roll, can be used.
[0038] The present invention will be further described below with reference to examples, but the scope of the present invention is not limited to these examples. EXAMPLES
[0039] Sixteen types of rubber compositions for side treads (Comparative Examples 1 to 6, In preparing Examples 1 to 10), the ingredients except for the vulcanization accelerator and sulfur were weighed. The mixture was mixed in a 1.8 L internal Banbury mixer for 5 minutes, and the master batch was discharged and stored at room temperature. After cooling, the master batch was placed in a 1.8 L internal Banbury mixer and mixed. The vulcanization accelerator and sulfur were added and mixed for 2 minutes to obtain each rubber composition for side tread. (Note that Example 6, in which butadiene rubber synthesized with a cobalt catalyst was used, and Examples 3 and 10, in which two types of butadiene rubber were used in combination and the proportion of butadiene rubber synthesized with a neodymium catalyst was less than 100 mass %, are reference examples.) .
[0040] The "Mc+Ms" column in Table 1 indicates the total amount of carbon black and silica. The "Ma / Ms" column in Table 1 indicates the ratio of the amount of vulcanization accelerator 2 (guanidine-based vulcanization accelerator) to the amount of silica. The "Ma / Mt" column in Table 1 indicates the ratio of the amount of vulcanization accelerator 2 (guanidine-based vulcanization accelerator) to the total amount of vulcanization accelerators (total of vulcanization accelerators 1 and 2).
[0041] Using each of the obtained rubber compositions for side tread, hardness, tensile strength, tan δ at 60° C., and breaking elongation retention were evaluated by the methods described below.
[0042] hardness Each rubber composition for side tread was vulcanized in a mold of a predetermined shape at 160°C for 20 minutes to prepare a vulcanized rubber test piece. The hardness of each vulcanized rubber test piece was measured using a type A durometer at a temperature of 20°C in accordance with JIS K6253. The evaluation results were expressed as an index with the value of Comparative Example 1 being 100. The larger the index value, the higher the hardness. Note that an index value of "98" or more means that a sufficient hardness equal to or greater than that of Comparative Example 1 was ensured.
[0043] Tensile strength Each rubber composition for side tread was used in a mold of a predetermined shape and vulcanized at 160°C for 20 minutes to prepare a vulcanized rubber test piece. Using these vulcanized rubber test pieces, JIS No. 3 dumbbell-shaped test pieces were cut out in accordance with JIS K6251, and a tensile test was performed at room temperature (20°C) at a tensile speed of 500 mm / min to measure the stress at break (break strength TB, unit: MPa). The obtained results are shown in the "tensile strength" column of Table 1 as an index, with the value of Comparative Example 1 set to 100. The larger this index value, the higher the tensile break strength. Note that if this index value is "99" or more, it means that sufficient tensile strength equivalent to or greater than that of Comparative Example 1 was ensured.
[0044] Tan δ at 60℃ Each rubber composition for side tread was used and vulcanized in a mold of a predetermined shape at 160°C for 20 minutes to prepare a vulcanized rubber test piece. For these vulcanized rubber test pieces, tan δ at 60°C was measured using a viscoelasticity spectrometer manufactured by Toyo Seiki Seisakusho Co., Ltd. under the conditions of initial strain of 10%, amplitude of ±2%, frequency of 20Hz, and temperature of 60°C. The evaluation results are shown in the "tan δ (60°C)" column in Table 1 as an index with the value of Comparative Example 1 set to 100. The smaller this value, the better the low heat buildup. Note that this index value of "99" is substantially the same as Comparative Example 1, meaning that no effect of improving low heat buildup was obtained.
[0045] Breaking elongation retention rate Each rubber composition for side tread immediately after being produced by the above method was vulcanized at 160°C for 20 minutes in a mold of a predetermined shape to prepare a vulcanized rubber test piece A. In addition, each rubber composition for side tread produced by the above method and left in an unvulcanized state for 30 days was vulcanized at 160°C for 20 minutes in a mold of a predetermined shape to prepare a vulcanized rubber test piece B. Using these vulcanized rubber test pieces A and B, JIS No. 3 dumbbell-shaped test pieces were cut out in accordance with JIS K6251, and a tensile test was performed at room temperature (20°C) at a tensile speed of 500 mm / min to measure the elongation at break (break elongation EB, unit: %) for each rubber composition for side tread. Then, for each rubber composition for side tread, the ratio (unit: %) of the break elongation measured by the vulcanized rubber test piece B to the break elongation measured by the vulcanized rubber test piece A was calculated, and used as an index of break elongation retention, which is shown in the "break elongation retention" column in Table 1. The closer this value is to 100%, the less the decrease in breaking elongation over time.
[0046] [Table 1]
[0047] The types of raw materials used in Table 1 are shown below. NR: Natural rubber, STR20 BR1: butadiene rubber synthesized using a cobalt catalyst, Nipol BR1220 manufactured by Nippon Zeon Co., Ltd. BR2: Neodymium-catalyzed butadiene rubber, ARLANXEO Buna CB24 BR3: Silica end-modified butadiene rubber, JSR BR511 CB1: Carbon black, Cabot Japan Co., Ltd. Show Black N550 (CTAB adsorption specific surface area: 40 m 2 / g) CB2: Carbon black, Cabot Japan Co., Ltd. Show Black N234 (CTAB adsorption specific surface area: 115 m 2 / g) ·Silica 1: Solvay 115GR (CTAB adsorption specific surface area: 110m 2 / g) ·Silica 2: Solvay 1165MP (CTAB adsorption specific surface area: 160m 2 / g) Silica 3: Solvay 1085GR (CTAB adsorption specific surface area: 80 m 2 / g) Silane coupling agent: Evonik Degussa Japan Si69 Aroma oil: Showa Shell Sekiyu Extract No. 4S Anti-aging agent 1: Santoflex 6PPD manufactured by Flexis Anti-aging agent 2: Nocrac 224 manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Wax: Paraffin wax manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Stearic acid: NOF Corp. bead stearic acid Zinc oxide: Three types of zinc oxide manufactured by Seido Chemical Industry Co., Ltd. Sulfur: Shikoku Chemical Industry Co., Ltd. Myucron OT-20 Vulcanization accelerator 1: Sulfenamide vulcanization accelerator, Noccela CZ-G manufactured by Ouchi Shinko Chemical Industry Co., Ltd. - Vulcanization accelerator 2: Guanidine-based vulcanization accelerator, Perkacit DPG manufactured by Flexsys
[0048] As is clear from Table 1, Examples 1 to 10 improved the low heat build-up property (tan δ at 60°C) while maintaining or improving the hardness and tensile strength to the same or higher levels compared to Comparative Example 1. Furthermore, Examples 1 to 10 were able to maintain good elongation at break compared to Comparative Example 1 even after being left in an unvulcanized state for 30 days.
[0049] On the other hand, in Comparative Example 2, the CTAB adsorption specific surface area of silica was large and no guanidine-based vulcanization accelerator was included, so the low heat generation property was deteriorated and the retention of elongation at break was also reduced. In Comparative Example 3, the particle size of silica was appropriate but no guanidine-based vulcanization accelerator was included, so the hardness, tensile strength, and retention of elongation at break were reduced. In Comparative Example 4, the amount of guanidine-based vulcanization accelerator was large compared to the amount of silica and the total amount of vulcanization accelerator, so the low heat generation property (tan δ(60°C)) was deteriorated. In Comparative Example 5, the amount of silica was large and the total amount of silica and carbon black was also large, so the low heat generation property (tan δ(60°C)) was deteriorated. In Comparative Example 6, the CTAB adsorption specific surface area of carbon black was large, so the low heat generation property (tan δ(60°C)) could not be improved.
[0050] The present disclosure includes the following inventions. Invention [1] A diene rubber containing 35% by mass to 55% by mass of isoprene rubber and 45% by mass to 65% by mass of butadiene rubber, the CTAB adsorption specific surface area of which is 60 m 2 / g~100m 2 / g silica, CTAB adsorption specific surface area is 30m 2 / g~100m 2 A rubber composition for a side tread, which is compounded with carbon black having a silica content of 0.1 to 0.5 parts by mass, a sulfur-containing silane coupling agent, and a guanidine-based vulcanization accelerator, wherein the amount of the silica compounded with respect to 100 parts by mass of the diene rubber is 5 parts by mass or more and 50 parts by mass or less, the total amount of the silica and the carbon black compounded is less than 55 parts by mass, and a ratio Ma / Ms of the amount of the guanidine-based vulcanization accelerator Ma to the amount Ms of the silica compounded is 0.02 to 0.08. The proportion of the butadiene rubber synthesized using a neodymium-based catalyst contained in the butadiene rubber is 100 mass %. A rubber composition for side treads, 。 Departure Light [ 2 The present invention is characterized in that other vulcanization accelerators other than the guanidine vulcanization accelerator are blended, and the ratio Ma / Mt of the blending amount Ma of the guanidine vulcanization accelerator to the total amount Mt of the vulcanization accelerator consisting of the guanidine vulcanization accelerator and the other vulcanization accelerator is 0.2 to 0.5. ] The rubber composition for a side tread described above. invention[ 3 The amount of the guanidine vulcanization accelerator is 0.5 parts by mass or more per 100 parts by mass of diene rubber. or [2] The rubber composition for a side tread according to claim 1. invention[ 4 Invention[1]~[ 3 13. A tire comprising a side tread rubber layer made of the rubber composition for a side tread according to any one of claims 1 to 12. [Explanation of symbols]
[0051] 1 Tread section 2 Sidewall 3 Bead section 4 Carcass layer 5 Bead Core 6 Bead Filler 7 Belt layer 8 Belt cover layer 10 Tread rubber layer 20 Side tread rubber layer 30 Rim cushion rubber layer CL Tire Equator
Claims
1. A diene rubber containing 35% by mass to 55% by mass of isoprene rubber and 45% by mass to 65% by mass of butadiene rubber, the CTAB adsorption specific surface area of which is 60 m 2 / g to 100m 2 / g, CTAB adsorption specific surface area is 30 m 2 / g to 100m 2 / g of carbon black, a sulfur-containing silane coupling agent, and a guanidine-based vulcanization accelerator, wherein the amount of the silica per 100 parts by mass of the diene-based rubber is 5 parts by mass or more and 50 parts by mass or less, the total amount of the silica and the carbon black is less than 55 parts by mass, the ratio Ma / Ms of the amount of the guanidine-based vulcanization accelerator Ma to the amount Ms of the silica is 0.02 to 0.08, and the proportion of butadiene rubber synthesized with a neodymium-based catalyst contained in the butadiene rubber is 100% by mass.
2. The rubber composition for side tread according to claim 1, characterized in that other vulcanization accelerators other than the guanidine-based vulcanization accelerator are blended, and a ratio Ma / Mt of a blending amount Ma of the guanidine-based vulcanization accelerator to a total amount Mt of the vulcanization accelerator consisting of the guanidine-based vulcanization accelerator and the other vulcanization accelerators is 0.2 to 0.
5.
3. 3. The rubber composition for side tread according to claim 1, wherein the compounding amount Ma of the guanidine vulcanization accelerator is 0.5 parts by mass or more based on 100 parts by mass of the diene rubber.
4. A tire comprising a side tread rubber layer made of the rubber composition for a side tread according to claim 1 or 2.
Citation Information
Patent Citations
Rubber composition for tire
JP2004256745A
Rubber composition for winter tire, and winter tire
JP2012224864A
Rubber composition for sidewall and pneumatic tire
JP2013018868A
JP2013‐001889A
Rubber composition for base tread
JP2014189774A
